Association between physical activity and cardiorespiratory factors in adolescents: a cross-sectional exploratory study - Rodrigues, Sara Daniela Quina (2015)
Background: Currently, under half of the adolescents reach recommended daily levels of physical activity (PA). It is known that higher levels of PA lead to higher levels of cardiorespiratory fitness (CRF) and therefore, a health-related CRF criterion value could contribute to identify the target population for primary cardiovascular disease prevention. Therefore, the aim of this study was to explore the relation between PA levels and CRF factors in healthy adolescents. Methods: A cross-sectional exploratory study with healthy adolescents aged 12-18 years old was conducted. Socio-demographic and body composition data were collected using a questionnaire. PA level was scored with the Physical Activity Index (PAI) and CRF assessment included lung function (LF) measured with spirometry and exercise tolerance measured with Incremental Shuttle Walking Test (ISWT). According to PAI scores the sample was divided in two groups: 1 (sedentary, low and moderately active); 2 (vigorously active (VA)). Descriptive statistics were applied to characterise the sample. Independent sample t-tests assessed differences between groups and simple logistic regressions identified the predictors of being VA. Results: The study included 115 adolescents (14.63±1.70 years old; 56.52% female). Adolescents presented a normal body mass index=21.19±3.14 Kg.m-2) and LF (forced expiratory volume in the first second (FEV1)=105.58±12.73% of the predicted). Significant differences were found between groups in height (G1–163.44±8.01; G2–167±8.65; p=0.024), LF (FEV1/ forced vital capacity (FVC); G1–97.58±10.66; G2–94.04±8.04; p=0.049), ISWT distance (G1– 1089.81±214.04; G2–1173.60±191.86; p=0.038); heart rate (HR) at rest (G1– 84.61±13.68; G2–79.23±13.81; p=0.038), HR at the end of the best ISWT (G1– 124.71±37.57; G2–133.54±33.61; p=0.041) and percentage of the maximal HR achieved during ISWT (G1–63.09±19.03; G2–67.53±17.08; p=0.043). Simple logistic regressions showed that height (OR–1.054; 95%CI 1.006-1.104), ISWT distance (OR–1.002; 95%CI 1.000-1.004) and HR at rest (OR–0.971; 95%CI 0.945-0.999) were predictors of being VA. Conclusions: Results suggest that more physically active adolescents have a better CRF profile. The findings suggest that PA is important to adolescents’ health status and it should be encouraged since childhood. Clinical practice will benefit from the use of PAI, ISWT and HR findings, allowing physiotherapists to use it for prescribing exercise.